Public - sector pay and adjustment - "Colclough, Christopher (ed.)" (London, 1997)
Changes to levels of earnings in the public and private sectors have a critical role in the adjustment process. Case studies of Singapore, Korea, Zambia, Zimbabwe and Argentina show that in those countries which adjusted unsuccessfully real earnings declined sharply, often with a further negative impact on output. The governments of the more successful East Asian adjusters influenced wage levels so as to help achieve their broader development goals. These case studies show that purely market-determined approaches to the labour market often failed.
Keywords: Structural adjustment